Diagnosis and management of paget's disease of bone - series of 8 cases - de Oliveira, Felipe Augusto Kazan [UNESP]; Pinto, Fábio Fernando Eloi [UNESP]; Sardenberg, Trajano [UNESP]; Pereira, Gilberto José Cação [UNESP]; Curcelli, Emílio Carlos [UNESP]; Penna, Valter [UNESP] (FapUNIFESP (SciELO), 2019)
Paget's disease of bone is a chronic condition characterized by focal abnormalities of absorption and formation of bone, and it may lead to anatomical deformities, pain, fractures, and malignant transformation. It is common in the UK, Australia, New Zealand, and North America and has a strong hereditary component, affecting first- to third-degree relatives. The etiology remains unclear and treatment is based on control of the disease with bisphosphonates, with the aim of relieving symptoms and correcting laboratory abnormalities. Surgical treatment may also be necessary to correct deformities or treat pathological fractures. This study evaluated the management and course of 8 patients with Paget's disease of bone, followed in the Orthopedic Clinic of this hospital. Among these patients, 1 had concomitant advanced prostate carcinoma, highlighting the association between Paget's disease and secondary bone diseases that can affect the differential diagnosis. Level of evidence IV, Study type: Case Series.

A doença de Paget óssea é uma afecção crônica, caracterizada por distúrbio focal da absorção e formação ósseas, podendo levar a deformidades anatômicas, dor, fraturas e malignização das lesões. é frequente no Reino Unido, Austrália, Nova Zelândia e América do Norte. Mantém forte relação de incidência com parentes de primeiro a terceiro graus. Sua etiologia ainda permanece incerta e o tratamento se baseia no controle da doença, com uso de bisfosfonados, visando melhora dos sintomas e das alterações laboratoriais. O tratamento cirúrgico também pode ser necessário, para correção de deformidades ou para tratamento de fraturas. Este estudo compilou oito pacientes em acompanhamento pela doença de Paget óssea, no Ambulatório de Ortopedia deste hospital, acerca do tratamento realizado e como evoluíram. Dentre os pacientes acompanhados, houve um caso de carcinoma de próstata concomitante ao Paget, chamando atenção para outras patologias ósseas que são diagnósticos diferenciais ou coexistem com a doença. Nível de evidência IV, Tipo de Estudo: Série de Casos.
Diagnóstico e manejo da doença de paget óssea - série de 8 casos
Keywords: Doença de paget; Metástase neoplásica; Neoplasm metastasis; Osteitis deformans; Osteíte deformante; Paget's disease